PVA/Chitosan/Silver Nanoparticles Electrospun Nanocomposites: Molecular Relaxations Investigated by Modern Broadband Dielectric Spectroscopy - Mohammad Hassan (8313699) (2018)
In this study, we used broadband dielectric spectroscopy to analyze polymer nanofibers of poly(vinyl alcohol)/chitosan/silver nanoparticles. We also studied the effect of incorporating silver nanoparticles in the polymeric mat, on the chain motion dynamics and their interactions with chitosan nanofibers, and we calculated the activation energies of the sub-Tg relaxation processes. Results revealed the existence of two sub-Tg relaxations, the first gets activated at very low temperature (−90 °C) and accounts for motions of the side groups within the repeating unit such as –NH2, –OH, and –CH2OH in chitosan and poly(vinyl alcohol). The second process gets activated around −10 °C and it is thought to be related to the local main chain segments’ motions that are facilitated by fluctuations within the glycosidic bonds of chitosan. The activation energy for the chitosan/PVA/AgNPs nanocomposite nanofibers is much higher than that of the chitosan control film due to the presence of strong interactions between the amine groups and the silver nanoparticles. Kramers–Krönig integral transformation of the ε′′ vs. f spectra in the region of the chitosan Tg helped resolve this relaxation and displayed the progress of its maxima with increasing temperature in the regular manner. Other Information Published in: Nanomaterials License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/nano8110888